2012
DOI: 10.2319/070111-425.1
|View full text |Cite
|
Sign up to set email alerts
|

A semi-automated method for bone age assessment using cervical vertebral maturation

Abstract: Objective: To propose a semi-automated method for pattern classification to predict individuals' stage of growth based on morphologic characteristics that are described in the modified cervical vertebral maturation (CVM) method of Baccetti et al. Materials and Methods: A total of 188 lateral cephalograms were collected, digitized, evaluated manually, and grouped into cervical stages by two expert examiners. Landmarks were located on each image and measured. Three pattern classifiers based on the Naïve Bayes al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 18 publications
1
17
0
3
Order By: Relevance
“…In addition, many studies (Alhadlaq and Al-Maflehi, 2013; Baccetti et al, 2006Baccetti et al, , 2002Baidas, 2012;Baptista et al, 2012;Choi et al, 2016;Flores-Mir et al, 2006;Franchi et al, 2000;Mito et al, 2003Mito et al, , 2002Uysal et al, 2006) revealed that the correlation for age and vertebral body height (using cervical vertebrae lateral radiography) or vertebral volume (using CT of cervical vertebrae), was strong and positive. However, these studies used different methodologies and were conducted on younger ages below 18 in order to detect maturation of cervical vertebrae as an age determination method in juveniles, which wasn't similar to the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies (Alhadlaq and Al-Maflehi, 2013; Baccetti et al, 2006Baccetti et al, , 2002Baidas, 2012;Baptista et al, 2012;Choi et al, 2016;Flores-Mir et al, 2006;Franchi et al, 2000;Mito et al, 2003Mito et al, , 2002Uysal et al, 2006) revealed that the correlation for age and vertebral body height (using cervical vertebrae lateral radiography) or vertebral volume (using CT of cervical vertebrae), was strong and positive. However, these studies used different methodologies and were conducted on younger ages below 18 in order to detect maturation of cervical vertebrae as an age determination method in juveniles, which wasn't similar to the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, different authors [27][28][29][30][31][32][33][34][35][36][37] proved strong positive correlation between age and vertebral body height (anterior, posterior and middle) on lateral radiography of cervical vertebrae or vertebral volume on CT of cervical vertebrae, however, these studies were conducted on young ages <18 years to identify cervical vertebral maturation as a method of age estimation in juveniles which was different from this study.…”
Section: Discussionmentioning
confidence: 56%
“…The hand-wrist radiograph has been used to assess stage of maturity of a child for a long time. To avoid taking additional radiographs, the cervical vertebral maturation method has become more popular method for assessment of skeletal maturity in recent years ( 3 , 10 , 11 , 12 , 13 , 14 , 16 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Errors induced from inadequate image segmentation could lead to false CVMI class assessment, therefore we adopted the approach that the second, third and fourth vertebrae contours are marked manually by the doctor. Unlike similar developed application s( 16 , 17 , 18 ), we propose to mark the entire contour instead of just few characteristical points. Thus, the shape features and characteristical points are extracted automatically and are more robust to marking errors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation